59 Short term elevation of cholesterol level in neonatal life and long term changes in aortic stiffness: insights from use of intravenous lipids. (9th June 2011) - Lewandowski, A J; Lazdam, M; Davis, E; Poole, R; Diesch, J; Francis, J; Neubauer, S; Lucas, A; Singhal, A; Kelly, B; Leeson, P
Abstract : Introduction: Offspring born to hypercholesterolaemic mothers have increased fatty streak formation in the fetal aorta, which persists into adolescence. To understand whether exposure to elevated cholesterol in early life, independent of a maternal history of hypercholesterolaemia, also has a long-term impact on the cardiovascular system we studied the vascular phenotype of adults in whom cholesterol levels were artificially elevated for a short period postnatally. Methods: We prospectively followed-up 102 subjects born premature now aged 23 to 28 years. Individuals exposed to maternal hypercholesterolaemia were excluded. 18 received intravenous (IV) lipids during the first nine weeks of life and were matched 2:1 for pregnancy and early life complications, age, sex, birthweight and gestational age with controls that did not receive IV lipids. Aortic pulse wave velocity (aPWV), regional aortic distensibility, left ventricular mass and ejection fraction were determined by cardiovascular magnetic resonance. Detailed lifestyle information and anthropometric measurements were collected during childhood and adolescence. Metabolic parameters were measured multiple times per week for the first 9 weeks of life and again at follow-up visits. Results: Individuals that received IV lipids achieved significantly higher maximum cholesterol levels during the first 9 weeks of life than those that did not (mean±SD=4.38±1.65 vs 3.12±0.78 mmol/l, p=0.006). Dose given and number of days on IV lipids also associated with maximum cholesterol level during this period (r=0.557, p<0.001 and r=0.567, p<0.001, respectively). There was a graded relation between the maximum elevation in circulating cholesterol postnatally and aortic stiffness (aPWV) in young adulthood (r=0.596, p<0.001). The greatest increase in stiffness was seen in the abdominal aorta, where distensibility was significantly reduced in the group that received IV lipids (mean±SD=9.74±4.27 vs 12.91±4.11/mm Hg×10 3, p=0.012). There were no differences between the groups in other vascular or left ventricular measures. In a stepwise regression model, maximum cholesterol level achieved in the first few weeks of life was an independent predictor of aPWV in young adulthood (β=0.596, p<0.001) and accounted for 30.9% of the variance in hierarchical multiple regression (β=0.584, p<0.001). Conclusions: Brief artificial elevation of cholesterol level in immediate postnatal life is associated with long term changes in aortic function independent of later cholesterol levels. The association is graded depending on the degree of elevation of circulating cholesterol. High cholesterol exposure during sensitive periods of early postnatal life may have long term impacts on the cardiovascular system.